Intelligent transport systems -- from research and development to the market uptake : first International Conference, INTSYS 2017, Hyvinkää, Finland, November 29-30, 2017, Proceedings /: first International Conference, INTSYS 2017, Hyvinkää, Finland, November 29-30, 2017, Proceedings. (2018) - Unknown
No abstract available